Primary-Secondary Wavelength Spectrophotometric Determination of Trace Amounts of Lignin Tannin in Water - Gao, Hong-Wen; Zhou, Jia-Gui (Asian Journal of Chemistry, 2010)
The conventional reaction of lignin and tannin with phospho-wolframate in the presence of sodium carbonate to form blue complex has been applied for the determination of trace amounts of lignin and tannin in water and wastewater by the updated method named primary-secondary wavelengths spectrophotometry (PSWS). The results show that the analytical precision and accuracy were increased and gave higher determining sensitivity than in ordinary spectrophotometry. The relative standard deviations were less than 3.1 % and the recovery rate of lignin and tannin were between 91.3 and 101 %.